Classroom composition and language skills: the role of school class and friend characteristics. Issue 8 (2nd September 2020) - Dollmann, Jörg; Rudolphi, Frida
Abstract: The present study addresses the question to what extent language skills among students are influenced by the composition of the overall classroom context and the composition of friendship networks within school classes. Furthermore, we ask whether the effects differ between stratified school systems, with a more homogenous student body in school classes, and comprehensive school systems, with a more heterogeneous student body. Focusing only on classroom characteristics, we find positive effects of the socioeconomic and cognitive overall composition of the school class in Germany's selective school system, but not in Sweden's comprehensive system. In contrast, the ethnic composition does not matter significantly in any of the systems, while direct peer interactions, captured with social networks measures targeting friends in a school class, matter slightly more in Sweden's comprehensive school system. Supplemental data for this article is available online at https://doi.org/10.1080/01425692.2020.1799754 .